Elimination of antiviral defense by viral RNase III - Cuéllar, Wilmer Jose; Kreuze, Jan F.; Rajamaki, M.L.; Cruzado, K.R.; Untiveros, M.; Valkonen, J.P.T. (National Academy of Sciences, 2009)
Sweet potato (Ipomoea batatas) is an important subsistence and famine reserve crop grown in developing countries where Sweet potato chlorotic stunt virus (SPCSV; Closteroviridae), a single-stranded RNA (ssRNA) crinivirus, synergizes unrelated viruses in co-infected sweet potato plants. The most severe disease and yield losses are caused by co-infection with SPCSV and a potyvirus, Sweet potato feathery mottle virus (SPFMV; Potyviridae). Potyviruses synergize unrelated viruses by suppression of RNA silencing with the P1/HC-Pro polyprotein; however, the SPCSV-SPFMV synergism is unusual in that the potyvirus is the beneficiary. Our data show that transformation of an SPFMV-resistant sweet potato variety with the double-stranded RNA (dsRNA)-specific class 1 RNA endoribonuclease III (RNase3) of SPCSV broke down resistance to SPFMV, leading to high accumulation of SPFMV antigen and severe disease symptoms similar to the synergism in plants co-infected with SPCSV and SPFMV. RNase3-transgenic sweet potatoes also accumulated higher concentrations of 2 other unrelated viruses and developed more severe symptoms than non-transgenic plants. In leaves, RNase3 suppressed ssRNA-induced gene silencing (RNAi) in an endonuclease activity-dependent manner. It cleaved synthetic double-stranded small interfering RNAs (siRNAs) of 21, 22, and 24 bp in vitro to products of approximately 14 bp that are inactive in RNAi. It also affected total siRNA isolated from SPFMV-infected sweet potato plants, suggesting a viral mechanism for suppression of RNAi by cleavage of siRNA. Results implicate RNase3 in suppression of antiviral defense in sweet potato plants and reveal RNase3 as a protein that mediates viral synergism with several unrelated viruses, a function previously described only for P1/HC-Pro.